MO781: Patients with Scarce Options for the First Arteriovenous Access: Lessons to be Learned from Vascular Mapping. (3rd May 2022) - Damas, Juliana; Barata, Rui; Assis Pereira, Tiago; Nolasco, Fernando
Abstract: BACKGROUND AND AIMS: The use of doppler ultrasound (DUS) is a non-invasive powerful tool, allowing the morphological and functional characterization of the blood vessels. Once an optimal location for vascular access (VA) creation is obtained, the risk of failure is reduced. Even the use of DUS has improved the VA creation, a significant proportion of patients remains with suboptimal VA, as the laborious umerobasilic fistulae or higher risk prosthetic fistula. Our aim was to identify patients with scarce VA options in the first VA planning, characterizing their demographical and clinical aspects, but also the ultrasound features that are described as having prognosis importance, mostly vessel diameter and calcification findings. METHOD: We retrospectively analysed a cohort of consecutive chronic kidney disease (CKD) patients that underwent DUS vascular mapping at a tertiary referral hospital from 2018 to 2019. All the DUS were performed by the same operator. Patient characteristics were collected. The DUS data observed were: arterial diameter and peak systolic velocity (VPS) in both arms, presence of mono- or biphasic waveform flow and calcification (quantified according to number of the involved arteries). We defined two groups for VA comparison—patients with scarce VA options (only umerobasilic fistula or prosthetic VA) versus patients whose mapping suggested availability for a radiocephalic or umerocephalic fistulae. Appropriate tests for continuous and categorical variables were applied, recurring to SPSS v21.0. Unadjusted and adjusted multivariate logistic regression models were fitted to determine which clinical or DUS findings were predictors for scarce VA options. RESULTS: A total of 153 patients were mapped by DUS, and 102 patients fulfilled the first VA creation criteria. The median age was 71 (58–79) years, 55 (54%) were male, 14 (14%) were black, 27 (28%) were already on dialysis or kidney transplantation. A total of 34 patients (33%) were identified as having scarce AV options, according to DUS. In patients with scarce VA options, there was a significant statistical difference between black race patients (0.042) and use of tobacco (0.041), within all the co-morbidities observed. Concerning arterial measurements, there was no difference in the arterial diameters. However, the radial PSV was lower in the group with fewer VA options (Table ). There were more arteries with calcification in these group. In the multivariate analysis, the arterial calcification was found to be a predictor for scarce VA options [odds ratio (OR) 1.26, 95% confidence interval (95% CI) 1.01–1.58], adjusted for the radial VPS measurements and black race. CONCLUSION: Starting haemodialysis with a matured and functional VA represents a successful outcome for CKD patients. Black race and arterial calcification score of the arteries were associated to suboptimal VA, which could identify these patients as having high-risk for morbidity and mortality related to VA. In our observation, the results were similar in both groups, whereas the main difference was on the radial PSV, which was consistently lower in the patients with fewer VA options. This finding showed that poorer radial haemodynamics precluded radiocephalic fistulae in these patients; otherwise, they are at higher risk for distal hypoperfusion ischaemic syndrome, which aggravates VA prognosis. The use of DUS is increasing in clinical practice due to its importance for the characterization of venous and arterial anatomy. This study, showed that high-risk patients for VA care can be identified before VA creation through a powerful tool as DUS, overcoming classical sociodemographic and clinical risk factors.